Implementasi Skor Fibrosis Non-Invasif (FIB-4, NFS) untuk Skrining MASLD di Layanan Primer Negara Berpenghasilan Menengah - Gusti Rama Dwitiya; Muhammad Zulfikar Rizki Aditya (Jurnal Riset Multidisiplin Edukasi, 2026)
Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) has become the leading cause of chronic liver disease in middle-income countries, with advanced fibrosis serving as the strongest prognostic determinant, yet limited access to liver biopsy and elastography in primary care settings necessitates the use of non-invasive fibrosis scores such as the Fibrosis-4 Index (FIB-4) and NAFLD Fibrosis Score (NFS). This narrative review was conducted through systematic searches in PubMed and Scopus from January 2015 to December 2024, focusing on studies reporting diagnostic performance or implementation experiences of FIB-4 and NFS in Asia and middle-income countries. Results demonstrate that FIB-4 offers operational superiority with negative predictive values reaching 90 to 99.7% at low cutoffs while requiring only four routine laboratory parameters, and two-tier algorithms using FIB-4 reduce unnecessary referrals by 60 to 75% without increasing missed diagnosis risk. In the Indonesian context, where MASLD prevalence reaches 51.0% (highest in Asia) and the Prolanis infrastructure routinely collects laboratory data from hundreds of thousands of high-risk patients, the potential for national-scale implementation is substantial but hindered by limited healthcare worker knowledge, laboratory method variability across facilities, and fragmented referral systems. This review concludes that FIB-4 is the most feasible score for fibrosis screening in primary care, with implementation requiring local cutoff validation, digital integration through the SATUSEHAT platform, laboratory standardization, continuous training, and strengthened tiered referral systems to transform approaches from reactive to proactive in preventing cirrhosis and hepatocellular carcinoma.